TYPOLOGICAL VARIATION IN ENCODING THE MANNER OF MOTION EVENT IN TRANSLATED VERSIONS OF ENGLISH AND TURKISH SHORT STORIES - İşler, Cemre (My University, 2022)
The aim of this study is to examine how speakers of typologically different languages, Turkish (a verb-framed language, V-language) and English (a satellite-framed language, S-language) express manner of motion events and how each language adapts itself to the demands of the other in translations with regard to the use of manner-of-motion verbs. In this respect, a total of 20 short stories (10 Turkish and 10 English) were selected to analyze. The effort was made to include the ones that are well suited for eliciting manner of motion verbs. For the identification of the motion verbs, Talmy’s (1985) definition of motion events was taken into consideration. According to the results, English writers were found to express manner of motion in their texts at a higher rate with regard to both token and type frequency of manner-of-motion verbs. As far as the translation strategies were considered, it was found that Turkish and English writers mostly used literal translation. In order to adapt the characteristics of the target language, it was also found that translators used a variety of strategies indicating compensation for language requirements.
Keywords: Linguistic typology; Motion events; Manner of motion verbs; S-languages; V-languages